High‐intensity interval training in chronic kidney disease: A randomized pilot study. (29th May 2019) - Beetham, Kassia S.; Howden, Erin J.; Fassett, Robert G.; Petersen, Aaron; Trewin, Adam J.; Isbel, Nicole M.; Coombes, Jeff S.
Abstract : Introduction: High‐intensity interval training (HIIT) increases mitochondrial biogenesis and cardiorespiratory fitness in chronic disease populations, however has not been studied in people with chronic kidney disease (CKD). The aim of this study was to compare the feasibility, safety, and efficacy of HIIT with moderate‐intensity continuous training (MICT) in people with CKD. Methods: Fourteen individuals with stage 3‐4 CKD were randomized to 3 supervised sessions/wk for 12 weeks, of HIIT (n = 9, 4 × 4 minute intervals, 80%‐95% peak heart rate [PHR]) or MICT (n = 5, 40 minutes, 65% PHR). Feasibility was assessed via session attendance and adherence to the exercise intensity. Safety was examined by adverse event reporting. Efficacy was determined from changes in cardiorespiratory fitness (VO2 peak), exercise capacity (METs), and markers of mitochondrial biogenesis (PGC1α protein levels), muscle protein catabolism (MuRF1), and muscle protein synthesis (p‐P70S6k Thr389 ). Results: Participants completed a similar number of sessions in each group (HIIT = 33.0[7.0] vs MICT = 33.5[3.3] sessions), and participants adhered to the target heart rates. There were no adverse events attributable to exercise training. There was a significant time effect for exercise capacity (HIIT = +0.8 ± 1.2; MICT = +1.3 ± 1.6 METs; P  = 0.01) and muscle protein synthesis (HIIT = +0.6 ± 1.1; MICT = +1.4 ± 1.7 au; P  = 0.04). However, there were no significant ( P  > 0.05) group × time effects for any outcomes. Conclusion: This pilot study demonstrated that HIIT is a feasible and safe option for people with CKD, and there were similar benefits of HIIT and MICT on exercise capacity and skeletal muscle protein synthesis. These data support a larger trial to further evaluate the effectiveness of HIIT.